Local available resources and indigenous knowledge, a tool to improve rural women livelihoods: the case of Umguza district ward 10, 13, 15, 16 and 17. - Sibanda, Privilege (Midlands State University, 2017)
Among many other groups of people, women are one of the most vulnerable groups in the world especially in the rural areas of the developing countries, including Zimbabwe. Women constitute 70% of the rural poor. This study focused on how rural women in the community of Umguza District in Matabeleland North Province have used local resources and indigenous knowledge to improve their livelihoods and the challenges they have faced along the way. The objectives of the study were to assess the livelihood outlook of women in Umguza District, to find out how women have used local resources and indigenous knowledge to improve their livelihoods and to identify the challenges that these women have faced in the use of these local resources and indigenous knowledge. The researcher opted for qualitative research and used open ended questionnaires and in-depth interviews to collect data from the relevant respondents. 44 participants were interviewed and the researcher opted for purposive sampling to select these participants. The research findings revealed that women in Umguza district have used the available local resources and indigenous knowledge to generate income, boost their food security and agricultural production, improve their lives in the health, sanitation and hygiene, education and transport sector.